The Influence of Review Quality and Review Quantity on Purchase Intention with Review Credibility as a Moderating Variable - Nanda Nazzha Meilani; Febzi Fiona (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The accelerated advancement of digital technology has reshaped consumer behavior, particularly in how purchasing decisions are made within e-commerce environments. In this landscape, online customer reviews serve as a crucial information source that shapes consumers’ purchase intentions. This study seeks to examine the effects of review quality and review quantity on purchase intention, moderated by review credibility. A quantitative approach with a causal explanatory design was employed, focusing on Indonesian e-commerce users across. Data were obtained through stratified random sampling, resulting in 260 qualified respondents who actively engage in online transactions and consistently read reviews prior to purchase. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that review quantity and review quality have positive and significant effects on both review credibility and purchase intention. However, review helpfulness and review credibility do not show a significant direct influence on purchase intention. Furthermore, review credibility significantly moderates the relationships between review quantity and purchase intention. The findings are anticipated to broaden the application of ELM within Indonesia’s e-commerce setting and offer managerial insights for practitioners seeking to strengthen consumer trust and purchase intention through the effective management of credible and informative online reviews.